Ambiente áulico y su influencia en el aprendizaje constructivista en los estudiantes de la Unidad Educativa María Astudillo de Babahoyo. 2022 - Chalé Merelo, Alex Enrique (2023)
Classroom learning environments are spaces where the teaching and learning process occurs between the teacher and the students, where students can feel comfortable in their space and are ready for learning, it is not limited to a physical space, it can be many contexts, Nowadays, learning spaces are flexible and ready to meet the needs of students, compared to traditional education, education has had a great change, for example, thanks to technology, virtual learning environments have been created. However, in a learning environment, it is very important to take into account that they must be adequate and ready to the needs of the students, ensuring that they can have a good displacement for both the teacher and the students, having the necessary memories. to condition the learning space, in addition to having a good relationship and communication within the classroom where the ideas of both the teacher and the student and among classmates flow, in this way a constructivist learning is achieved, where the student develops by himself creating your own knowledge. The constructivist method is the way that the teacher has to work with the students, helping the student to acquire their knowledge by themselves, thanks to the resources found in their learning spaces, constructivist learning is about the student make mistakes and through them be able to learn, the student builds his own knowledge and learns at his own pace, it is necessary for the teacher to know the learning pace of the students since everyone learns differently and get used to and be patient in this process.